The privacy mission : achieving ethical data for our lives online - Machon, Annie (John Wiley & Sons, Inc., 2023)
"The subject of data ethics has never been more urgent. This is no longer an academic or niche geek issue as it has been since the inception of the internet and the world wide web. Data ethics is an issue that affects all our lives as we have been forced by covid to live increasingly online. Who controls access to the hardware, who runs the software, who can spy on us, hack us, data farm us? What are the threats that we need to mitigate against democratically, societally and personally? How can corporations protect us rather than predate on us, and how can that help their bottom line? In this book I aim to summarise both the overarching concepts and principles about why this is important, and offer practical solutions for companies, policy makers, academia and individuals to push back against these known threats and also try to future proof themselves going forward. This is information we all need to know and apply as technology accelerates exponentially"--